Near-Infrared Spectrometry of Stone Celts in Precontact British Columbia, Canada. Issue 3 (July 2015) - Morin, Jesse
Abstract : Research into broad patterns of trade and exchange in precontact British Columbia, Canada, has been very limited. This paper addresses that shortcoming by presenting the results of a mineralogical study of 1, 374 stone celts and 131 sawn cores from which celts were manufactured from 196 archaeological sites across British Columbia. These artifacts were an integral part of the woodworking toolkits of aboriginal peoples in this region from ca. 3500 B.P. to around contact at about 180 B.P. The mineralogy of these artifacts was determined using a portable near-infrared spectrometer, and the resulting data mapped using Geographic Information Systems. The results of this study indicate that celt production and exchange largely occurred within five discrete celt stone regions. For two of these celt stone regions—the Salish Sea and the Canadian Plateau—1 argue that these represent interaction spheres. Only in the Salish Sea were considerable numbers of celts imported from another region. For the remaining three regions, not enough data are available on the geological distribution of various celt stones or on the spatial patterns of celt production to differentiate regional interaction from individual procurement and production.